Pilot Study of a Modified DOPS Scale for Insulin Pump and CGM Installation Training in Chinese Medical Students During Endocrinology Rotations - Yuan Y; Wang C; Wen S; Li Y; Xu C; Yu F; Li X; He Y; Chen L; Ren Y; Zhou L (Diabetes, Metabolic Syndrome and Obesity)
Yue Yuan,1,* Congcong Wang,1,* Song Wen,1,* Yanyan Li,1 Chenglin Xu,1 Fang Yu,1 Xiucai Li,1 Yanju He,1 Lijiao Chen,1 Yishu Ren,1 Ligang Zhou1,2 1Department of Endocrinology, Shanghai Pudong Hospital, Fudan University, Shanghai, 201399, People’s Republic of China; 2Shanghai Key Laboratory of Vascular Lesions Regulation and Remodeling, Shanghai Pudong Hospital, Fudan University, Shanghai, 201399, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ligang Zhou, Department of Endocrinology Shanghai Pudong Hospital Fudan University, Shanghai, 201399, People’s Republic of China, Tel +008613611927616, Email zhouligang1n1@163.comBackground: Direct Observation of Procedural Skills (DOPS) is a clinical assessment tool that enables trainers to observe medical students’ procedural abilities in real-time clinical settings. It assesses students’ knowledge application, decision-making, and skill proficiency during clinical tasks.Methods: This study modifies the DOPS to evaluate the operation of insulin pumps (PUMP) and continuous glucose monitoring systems (CGMS) in diabetes management. Key elements of the modified DOPS include 1) Knowledge Assessment: Evaluating understanding of PUMP and CGMS, including interpreting CGMS data for insulin adjustments; 2) Operational Skills: Assessing correct PUMP needle insertion, programming, and adjustments; 3) Patient Safety: Ensuring safe and aseptic procedures; 4) Feedback: Providing constructive feedback to help students improve their skills.Results: Training through DOPS led to significant improvements in all domains, overall performance scores, and reduced execution time for each domain. Correlations between domains showed that PUMP indication scores were linked to all other domains and execution times, including re-evaluation. Communication skills and seeking assistance were crucial factors influencing other domains. Multilinear regression analysis revealed that while DOPS-CGMS (R square 1.0) fully explained performance scores, DOPS-PUMP (R square 0.984) indicated that additional personal qualities significantly impacted students’ PUMP operation performance.Conclusion: This customized DOPS form offers insights into students’ abilities in managing diabetes with PUMP and CGMS, while emphasizing the need for training on both technical skills and interpersonal skills in future educational models.Keywords: diabetes mellitus, direct observation of procedure of skills, insulin pump, continuous glucose monitor system